RELASI BAHASA DAN IDEOLOGI - Mubaligh, Ahmad (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2010)
Language is an arbitrary code system having close relationship with the ideology, because in any use of the language is ideological. According to linguists language is ideology. The relationship between language and ideology is in its language use and materializing the language in ideology. Words used and the meaning coming up from the words show someone’s position in a certain social class. Language becomes a battle site for many groups and class who take great effort to instill its belief and perceiving. In addition, the relationship of language and ideology can also be seen from its use not only as a means of communication but also language as a tool to influence, change and dominate other people so that the reader or audience will receive and justify the messages, ideas, and thought delivered, even to believe and follow it.